Analisis Pengaruh Penerapan SIMRS Terhadap Kinerja Pegawai di Unit Rawat Jalan RSUD X - Firdaus, Muhammad; Tonis, Marian; Bisra, Marido; Zaky, Abdul; Handoko, Bobi; Rifly, Nadya Faradhifa (STIKES Yayasan RS.Dr.Soetomo, 2024)
Hospital Management Information System abbreviated as SIMRS is an information technology system that is a system that can process everything in the hospital in the form of coordination networks, reporting and administrative procedures to obtain precise and accurate information. SIMRS is one of the components that can affect employee performance where SIMRS helps employees in completing all services. The purpose of this study was to see the effect of SIMRS in improving employee performance. This research uses quantitative research with descriptive methods conducted at Arifin Achmad Hospital, Riau Province. This research was conducted through distributing questionnaires with 67 respondents, namely Outpatient Employees of RSUD Arifin Achmad Riau Province who use SIMRS. The results of this study obtained from the processing of research data show that the influence of SIMRS has a significant effect on the Performance of the Outpatient Unit of the Arifin Achmad Hospital Riau Province. This can be seen with a sig value of 0.002 <0.05.